Response of the stingless bee manduri do mato grosso (Melipona favosa orbignyi, Hymenoptera, Apidae) to variable concentrations of sucrose in artificial feeding sources of different colors - Brizola-Bonacina, Anna Kátia [UNESP]; Alves-Junior, Valter Vieira; Chaud-Netto, José [UNESP] (My University, 2009)
Three nests of Meliponafavosa orbignyi were used to register the frequency of workers' visits to artificial feeding sources of different colors, containing variable concentrations of sucrose. In the first series of experiments feeders of the same color containing syrup with 20, 50 and 80% sucrose were used. In the second phase of the research the feeding sources had different colors (blue, white, yellow and orange) and sucrose syrup with the same concentration. The source that contained syrup with 50% sucrose and blue color was the most visited by the workers of M.f. orbignyi.
Keywords: Artificial source; Discrimination; Forager bees; Gathering of food; Melipona; Apidae; Apoidea; Hymenoptera; Melipona favosa; Meliponinae; Micromesistius poutassou